Sport Marketing (Hillary Commission for Sport, 2024)
Topics in the series include: Legal Obligations of Boards, Strategic Planning, Policy Development, Financial Management, Sport Marketing, Public Relations, Recruitment and Selection, Volunteer and Staff Management, Strategic Leadership.